A Springback Compensation Strategy and Applications to Bending Cases. Issue 5 (18th December 2012) - Liao, Juan; Xue, Xin; Zhou, Chi; Barlat, Frederic; Gracio, Jose J.
Abstract Part shape error due to springback is a manufacturing defect in the sheet metal forming. This problem can be corrected by adjusting the tool shape to an appropriate shape or process optimization. In this paper, a discrete curvature adjustment (DCA) strategy is developed for tool design of channel bending products. This strategy aims at generating the right tool shape in a short time using the measured data from the trial part. A dynamic compensation factor which varies with part geometry and specific process condition will also be used to adjust the tool curvatures. Applications of this method in the tool design of an asymmetrical U‐shaped part, an industrial blade, and a cylindrical part were presented. The experiment results demonstrated that this strategy was able to reduce the trial times of die modification from five or six to one or two, thus saving time and cost in the industry production. Additionally, the comparison of this method with the existing displacement adjustment (DA) method was also discussed.